Case report: Variability in clinical features as a potential pitfall for the diagnosis of Barth syndrome - Tovaglieri, Nicola; Russo, Silvia; Micaglio, Emanuele; Corcelli, Angela; Lobasso, Simona (Frontiers in Pediatrics, 2023)
Barth syndrome is a rare genetic disease characterized by cardiomyopathy, skeletal muscle weakness, neutropenia, growth retardation and organic aciduria. This variable phenotype is caused by pathogenic hemizygous variants of the TAFAZZIN gene on the X chromosome, which impair metabolism of the mitochondrial phospholipid cardiolipin. Although most patients are usually diagnosed in the first years of life, the extremely variable clinical picture and the wide range of clinical presentations may both delay diagnosis. This is the case reported here of a man affected with severe neutropenia, who was not diagnosed with Barth syndrome until adulthood.We describe herein a family case, specifically two Caucasian male cousins sharing the same mutation in the TAFAZZIN gene with a wide phenotypic variability: an infant who was early diagnosed with Barth syndrome due to heart failure, and his maternal cousin with milder and extremely different clinical features who has received the same diagnosis only at 33 years of age.Our report supports the underestimation of the prevalence of Barth syndrome, which should be always considered in the differential diagnosis of male patients with recurrent neutropenia with or without signs and symptoms of cardiomyopathy.